El neo-humanismo chino: un nuevo paradigma jurídico e internacional - Staiano, Maria Francesca (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2020)
In this article we propose the concept of Chinese neohumanism to interpret the current Chinese internal reform process and China's international positioning. Although similar currents and ideas had already emerged in the history of China, the analysis will focus on the innovative aspects of the current Chinese reformist trajectory. In fact, it is argued that elements of “neo-humanist” thought in China have revealed their influence on international law and relations. The drafting of the new Civil Code of the People's Republic of China, approved in May 2020, and the construction of new theories and practices of international relations, especially the adoption of the concept of “Community of Shared Future for Mankind”, offer many contents to interpret through a circular thought the construction of a system that stands as a people-centered approach (“people-centrism”), generating a new humanism. Likewise, the analysis aims to find the elements of the Chinese humanist process in international relations with Latin America.